2008
DOI: 10.1111/j.1600-0501.2008.01612.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observation of 41 perforations of the Schneiderian membrane during sinus floor elevation

Abstract: With appropriate treatment, intraoperative sinus membrane perforations did not represent an elevated risk for implant loss, infectious complications or displacement of graft material in the investigated population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
180
2
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(206 citation statements)
references
References 16 publications
13
180
2
11
Order By: Relevance
“…They concluded that the sinus membrane perforation was not shown to be a significant factor in the rate of implant complications. Numerous case reports of accidental sinus perforation during implant placement conclude that the perforation did not lead to any serious sequela or morbidity [8] [9].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the sinus membrane perforation was not shown to be a significant factor in the rate of implant complications. Numerous case reports of accidental sinus perforation during implant placement conclude that the perforation did not lead to any serious sequela or morbidity [8] [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, with large sinus membrane perforations, some authors recommend aborting the sinus augmentation procedure due to the higher percentage of implant failures associated with such large perforations [6,7,9,16,29,[38][39][40]. An alternative strategy is to repair the large sinus membrane tear or perforation using a bioresorbable collagen membrane and platelet rich plasma, but without adding the bone graft material.…”
Section: Management Of the Large Perforated Or Completely Torn Schneimentioning
confidence: 99%
“…Die Perforation der Schneider-Membran ist mit 12-44 % die häufigste intraoperative Komplikation. Bei adäquater Versorgung scheinen Perforationen die Implantatüberlebensrate jedoch nicht negativ zu beeinflussen (Becker et al 2008 sind Mund-Antrum-Verbindungen (10 %), Hämatome (7,4 %), Sinusitis (7,3 %), Wundinfektion (5,0 %), Verlust des Augmentats (3,1 %), Verschluss des Ostium naturale (2,5 %) und Zystenbildung in der Kieferhöhle (1,2 %;Schwartz-Arad et al 2005).…”
Section: Komplikationen Sinusbodenelevationunclassified